2001
DOI: 10.1017/s1357729800052103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of type and treatment of grain and protein source on dairy cow performance

Abstract: The effects of different types of energy or protein supplementation on performance of cows given grass silage-based diets were studied. The possibility of maintaining high energy intakes by using different grain sources, barley or maize, or by the use of the physical processing of the barley was investigated. In addition, the relative quality of rapeseed meal as a protein supplement compared with alternative protein supplements was examined. In experiment 1 16 Finnish Holstein-Friesian cows were used in a cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
7
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 34 publications
6
7
3
Order By: Relevance
“…Concentrate starch source The lack of effects from replacing barley-with maize-based concentrate on cows' DMI were consistent with the findings of Khalili et al (2001) but not with those of others (McCarthy et al, 1989;Overton et al, 1995;Silveira et al, 2007), who observed a reduction in the DMI of cows on barley-based diets. The diets and other experimental conditions used in the study reported herein differed from those in which feeding with barley-based concentrates resulted in DMI reduction but similar to those of Khalili et al (2001).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Concentrate starch source The lack of effects from replacing barley-with maize-based concentrate on cows' DMI were consistent with the findings of Khalili et al (2001) but not with those of others (McCarthy et al, 1989;Overton et al, 1995;Silveira et al, 2007), who observed a reduction in the DMI of cows on barley-based diets. The diets and other experimental conditions used in the study reported herein differed from those in which feeding with barley-based concentrates resulted in DMI reduction but similar to those of Khalili et al (2001).…”
Section: Discussionsupporting
confidence: 85%
“…We were unable to explain the observed greater NDFD in B diets in our study, thereby speculating that increased iNDF levels in M diets may be responsible. A similar observation regarding the effect of increased proportional contribution of concentrate NDF on the total NDFD has been made by Khalili et al (2001).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations